Evidence use in E-cigarettes debates: scientific showdowns in a 'wild west' of research - Katherine E. Smith; Theresa Ikegwuonu; Heide Weishaar; Shona Hilton (BMC, 2021)
Abstract Background Against a backdrop of declining tobacco use, e-cigarette markets are growing. The UK now has a higher percentage of e-cigarette users than any other European country. These developments have prompted fierce discussions in scientific, advocacy and policy communities about how best to respond. This article is one of the first to examine the role of evidence in these debates. Methods We analysed 121 submissions to two Scottish policy consultations on e-cigarettes (in 2014 and 2015) and undertook interviews with 26 key informants in 2015-2016, following up with a sub-set in 2019-2020. All data were thematically coded, and our analysis was informed by insights from policy studies and the sociology of science. Results First, we affirm previous research in suggesting that e-cigarettes appeared to have triggered a breakdown of old public health alliances. Second, we demonstrate that, amid concerns about research quality and quantity, actors are guided by normative outlooks (and/or economic interests) in their assessments of evidence. Third, we show that, despite describing e-cigarette debates as contentious and polarised, actors engaging in Scottish policy debates exhibit a spectrum of views, with most interviewees occupying an uncertain 'middle ground' that is responsive to new evidence. Fourth, we suggest that the perceived divisiveness of e-cigarette debates is attributed to recurrent media simplifications and tensions arising from the behaviours of some actors with settled positions working to promote particular policy responses (including by strategically enrolling supportive evidence). Fifth, we argue that the actions of these actors are potentially explained by the prospect that e-cigarettes could usher in a new tobacco 'policy paradigm'. Finally, we show how scientific authority is employed as a tool within these debates. Conclusions E-cigarette debates are likely to reconcile only if a clear majority of participants in the uncertain 'middle ground' settle on a more fixed position. Our results suggest that many participants in Scottish e-cigarette debates occupy this 'middle ground' and express concerns that can be empirically assessed, implying evidence has the potential to play a more important role in settling e-cigarette debates than previous research suggests.